EFFECT OF COOPERATIVE LEARNING STRATEGY ON STUDENTS' ACADEMIC ACHIEVEMENT AND INTEREST IN FINANCIAL ACCOUNTING IN ABIA STATE (NAU Journal of Technology and Vocational Education, 2024)
This study determined the effect of cooperative learning strategy on secondary school students'academic achievement and interest in Financial Accounting in Abia State. Two researchquestions and two null hypotheses guided the study. The design of the study was quasiexperimental design, with pretest and posttest non-equivalent control group. The population ofthe study comprised 846 public senior secondary school two (SS 2) students in Abia State. Asample of 55 students was drawn using purposive sampling technique for the study. Theinstruments for data (achievement test – FAAT, and interest questionnaire – FAIQ) werevalidated by three experts. Reliability coefficients of 0.80 and 0.79 were obtained using KudderRichardson formula 20 and Cronbach’s alpha respectively. Mean and standard deviation wereused to answer the research questions and ANCOVA was used to test the null hypothesis at 0.05level of significance. The findings revealed that the students taught financial accounting usingcooperative learning strategy performed better than their counterparts taught using lecturemethod. Also, cooperative learning strategy enhanced the interest of students more than thosetaught using lecture method. Based on the findings of the study, it was concluded thatcooperative learning strategy has proved to be more efficacious in enhancing students’ academicachievement and interest in Financial Accounting than lecture method. Two recommendationswere made based on the findings of the study
Keywords: Cooperative Learning, Academic Achievement, Financial Accounting, Interest Introduction